Influence of Surcharge Loading, Retained Soil and Restrained Soil on Design of Diaphragm Wall - Nu Nu Win; Nyan Myint Kyaw; Khin Than Yu (Institut Teknologi Sepuluh Nopember, 2017)
Many different types of embedded retaining wall are constructed due to the increasing demands. In Yangon, Myanmar is encountered deep excavation problem. Many buildings are damaged due to excavation of adjacent building. Therefore, embedded retaining wall as excavation support system is necessary to be sustainable buildings. There are important that influence of surcharge loading, retained soil and restrained soil on design of embedded retaining wall. In this paper, diaphragm Wall is emphasized and solved using soil structure interaction analysis. Behaviour of diaphragm Wall wall is based on various factors. Consider with natural and increasing of shear strength parameter of retained and restrained soils to get the level of the dredge line is stiff soil and various distances from wall to surcharge. Sites are located in urban setting, there are near building and separately from main structure. This project involves the construction of 5 m depth retaining wall. In case study (A) retained soils is soft, medium (low) clay, restrained soil is mostly cohesive soil. There are medium (low), stiff, medium, hard soil layers. In case studies (B to H) are increasing shear strength parameter of retained soil and restrained soil. All cases are considered with various distances from wall to surcharge. According to the soil conditions and distance from wall to surcharge, Wall depth, horizontal and vertical movement of ground and wall deflection are described. When retained and restrained soil reach stiff condition, then ground movement and wall deflection reach acceptable limit and wall depth become more safe and economical condition.